Bulaklak ng Maynila (Viva Films, 1999)
The daughter of impoverished parents, Ada's life becomes even more miserable when her father is imprisoned after attempting to rob a bank. For them to survive, Ada and her mother live with Timo, who makes their lives miserable. Ada leaves home and becomes a sexy dancer to survive.